Українська "жіноча" пісня: до питання становлення терміна - Михалевич, Ірина; Mykhalevych, Iryna (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена неоднозначному питанню жанротворення необрядової пісенності. На основі фольклористичних студій, здійснених дослідниками в ХІХ ст., простежено становлення терміна «жіноча» пісня. Здійснено детальний огляд праць, які висвітлюють історію розвитку цього жанрового різновиду лірики.The historical formation of this term is shown in the suggested article.On the basis of the folklore works,made by researches in the 19th century, a detailed review of works is completed. These works highlight the ambiguous position on this issue. This allows you to follow the changes and transformations of the term, that marks the concept of the lyris song in the women’s performance. Despite the existence of several classifications of nonritual folk-texts, the only theoretically justified classification still does not exist. The main theoretical achievements and works of folk art collections are outlined in this article, where the attempts of folk poetry classifications are contained. By these achievements in the field of ethnography, archeology, folklore and romance a solid foundation for further scientific achievements was laid.
Ukrainian “Women’s” Song: On the Topic of the Terms’ Formation
Keywords: жіноча пісня; лірика; жанровий різновид; ліричний герой; пісня про кохання; the women’s song; genre variety; Mychailo Maksymovych; Mykola Kostomarov; Ivan Franko; lyrics; the lyrical hero; the song about love